Bilateral nasolabial cysts: a case report. (December 2016) - Sato, Masaru; Morita, Keiichi; Kabasawa, Yuji; Harada, Hiroyuki
Abstract Background Nasoalveolar cysts are rare non-odontogenic cysts that occur beneath the nasal alar region. Few cases of bilateral nasoalveolar cysts have been described. Case presentation We report a rare case of a 67-year-old Japanese woman with bilateral nasoalveolar cysts who presented to our department with the chief complaint of a swollen left nasal alar base. Panoramic radiography revealed no abnormalities. Computed tomography and magnetic resonance imaging revealed a well-circumscribed oval lesion at both alar bases. Therefore, bilateral nasoalveolar cysts were clinically diagnosed. Furthermore, these cysts were extirpated under general anesthesia; the aforementioned diagnosis was histopathologically confirmed. No recurrence has been observed 1 year after surgery. Conclusions Nasoalveolar cysts are rare. It is necessary to be careful because nasoalveolar cysts can show bilateral occurrence.